1982
DOI: 10.3928/0147-7447-19820101-09
|View full text |Cite
|
Sign up to set email alerts
|

The Percutaneous Lateral Retinacular Release

Abstract: A lateral retinacular release performed through a 2 ½-3 cm lateral parapatella incision can give rewarding results for patients with chondromalacia, degenerative joint disease, recurrent subluxation or recurrent dislocation of the patella. A retrospective review from August 1978 to December 1980 of 37 patients (42 knees) shows 83% excellent or satisfactory results, 17% unsatisfactory results with an average postoperative follow-up of 12.3 months. Preoperative pain was reduced in all but two patients; no patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The misuse and improper use of LRR has brought about undesirable results and complications (Sanchis-Alfonso, Montesinos-Berry et al, 2015). Nevertheless, some current studies also indicate that the overall effect of LRR is not sustainable in the long term(Betz, Lonergan et al, 1982;Dandy and Gri ths, 1989;Dandy and Desai, 1994). Desio et al(Desio, Burks et al, 1998) found that lateral patellar stability decreased by 10% at the knee exion 20° after LR released, The structure relaxation may enhance patellar instability.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The misuse and improper use of LRR has brought about undesirable results and complications (Sanchis-Alfonso, Montesinos-Berry et al, 2015). Nevertheless, some current studies also indicate that the overall effect of LRR is not sustainable in the long term(Betz, Lonergan et al, 1982;Dandy and Gri ths, 1989;Dandy and Desai, 1994). Desio et al(Desio, Burks et al, 1998) found that lateral patellar stability decreased by 10% at the knee exion 20° after LR released, The structure relaxation may enhance patellar instability.…”
mentioning
confidence: 93%
“…An amount of factors have been demonstrated in the pathogenesis of patellofemoral instability. When combined with other factors (including dysplastic trochlear, dysplastic patella, or an abnormal Q angle, the damage of medial parapatellar soft-tissue) (Arendt, Fithian et al, 2002;Fithian, Paxton et al, 2004a;Stefancin and Parker, 2007) the isolated use of a lateral retinacular release of the patella for the therapy of patellar instability is improper (Betz, Lonergan et al, 1982;Dandy and Gri ths, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation